Holding the dream - Roberts, Nora; Copyright Paperback Collection (Library of Congress) (New York Jove Books, 1997)
Kate Powell faces a professional impropriety and a dark secret from her past that forces her to search deep within herself
1
Keywords: Friendship -- Fiction; Monterey (Calif.) -- Fiction; Historical fiction